Adherence to antihypertensive medication and hypertensive emergencies - Yunita Aisah Putri; Shinta Arini Ayu; Ricko Dwi Haryanto (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Hypertension is a non-communicable disease with a high prevalence and potential to cause serious complications, including hypertensive emergencies. One of the important factors in preventing this condition is adherence to antihypertensive medication. Purpose: To determine the relationship between adherence to antihypertensive medication and the incidence of hypertensive emergencies. Method: A quantitative design with a correlational analytic approach and cross-sectional design was employed. The sample consisted of 109 respondents selected using accidental sampling technique. Data were collected using questionnaires and analyzed using Chi-Square test with a significance level of 0.05. Results: Most respondents had low adherence to antihypertensive medication (67.9%). The majority did not experience hypertensive emergencies (68.8%), while 31.2% experienced such events. Statistical analysis showed a p-value of 0.001 (p < 0.05), indicating a significant relationship between medication adherence and hypertensive emergencies. Conclusion: Higher adherence to antihypertensive medication reduces the risk of hypertensive emergencies. Efforts are needed to improve adherence through education, routine monitoring, and strengthening the role of healthcare workers.